Assessment for Sustainable Transportation Systems in Egypt - Fares, Hagar Mohamed (AUC Knowledge Fountain, 2024)
The assessment of a sustainable transportation system poses a significant challenge for local governments, as it dramatically influences the promotion of environmentally friendly modes of transportation with the objective of safeguarding the public's welfare and health in their daily activities. The integration of such assessment should be implemented from the initial stages of system planning to its operational and maintenance phases, particularly in light of the increasing number of urban development activities nationwide. In order to facilitate decision-making processes, it is imperative to establish an efficient rating system that incorporates cultural and social constraints and comprehensively considers the three dimensions of sustainable development: economic, environmental, and social. Therefore, creating and evaluating social sustainability in transport projects is doable. This study seeks to identify existing sustainability certification programs and their criteria. According to the outcomes of this study, those certification systems do not prioritize the inclusion of measures to assess social sustainability compared to environmental and economic sustainability. Based on the importance of assessment tools for sustainable transport in Egypt, this study proposes an applicable assessment tool focusing more on social sustainability. In this research new assessment tool has been developed to probe for a set of criteria that a transport project is recommended to follow in order to be sustainable. The criteria were adopted from the review of the literature and existing tools, which suggested the division of the new system into six categories: project requirements, environment and water, construction activities, materials and design, utilities and control, and access and livability. Once the tool was developed it is tested on the Greenline High-Speed Rail Project (Ain Sokhna – Marsa Matrouh). This project is an ideal case study since it is currently under construction, making it the most suitable time for evaluation. After management-level experts assess the project, corrective actions can be taken immediately before the operation phase starts. Also, those professionals who proposed minor adjustments evaluated the applicability of the developed system. It was found that the majority of the experts are more likely to use the new tool, and they find it applicable to be used in infrastructure transport projects in Egypt. Besides, faculty members with experience in transportation engineering were interviewed as an additional evaluation method, and they provided thorough feedback on the applicability of the local system. The objective of this study is not to provide a tool as a final outcome but rather to propose it as a base for future research and for professionals, including concerned governmental authorities and consultants, to develop and enhance. The specific characteristics of the tool may differ in different contexts. However, at least a basic framework and methodology can be derived from this study, which may serve as a foundation for future research.